2020
DOI: 10.3390/insects11090573
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Horizontal Edge–Interior and Vertical Canopy–Understory Gradients on the Abundance and Diversity of Bark and Woodboring Beetles in Survey Traps

Abstract: Semiochemical-baited intercept traps are important tools used to collect information about the presence/absence and population dynamics of forest insects. The performance of these tools is influenced by trap location along both horizontal edge–interior and vertical understory–canopy gradients. Consequently, the development of survey and detection programs requires both the development of effective traps and semiochemical lures but also deployment protocols to guide their use. We used field trapping experiments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 52 publications
(67 reference statements)
1
10
0
Order By: Relevance
“…A similar result was also observed for ALB, which was caught in higher numbers by traps hanging from trees than from bamboo poles (Nehme et al., 2010). Other researchers have found traps placed under the canopy or in the forest edges to be more effective in catching long‐horned beetles than traps set up in clearings and open fields (Dodds, 2011; Sweeney et al., 2020). According to the results of our study, the protocol that provides the highest levels of CLB captures is therefore the installation of cross‐vane traps in the crowns of CLB host trees.…”
Section: Discussionmentioning
confidence: 99%
“…A similar result was also observed for ALB, which was caught in higher numbers by traps hanging from trees than from bamboo poles (Nehme et al., 2010). Other researchers have found traps placed under the canopy or in the forest edges to be more effective in catching long‐horned beetles than traps set up in clearings and open fields (Dodds, 2011; Sweeney et al., 2020). According to the results of our study, the protocol that provides the highest levels of CLB captures is therefore the installation of cross‐vane traps in the crowns of CLB host trees.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when using traps with α-pinene, ethanol, ipsdienol, and ipsenol, it turned out that species richness, species diversity, abundance, number of unique species of Coleoptera were higher in the undergrowth compared to traps under the canopy [32]. The average catch of Dicerca divaricata in traps with sex attractants was significantly lower in the undergrowth than in any other trap locations [33]. Catches of Monochamus galloprovincialis in traps with various attractants located in tree crowns were significantly larger than in traps located at lower forest strata [34].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, several recent studies have shown that trap placement can significantly affect trap captures of arboreal insects [ 25 , 26 ], including cerambycids, with some species being caught primarily at ground level, whereas others were caught preferentially by traps in the canopy [ 10 , 27 , 28 , 29 , 30 ]. These reports suggest that different species prefer different strata within the tree canopy, possibly as a function of their differing requirements for either standing or fallen trees as hosts, and trunks versus branches.…”
Section: Introductionmentioning
confidence: 99%